(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: the Hajj is mandatory practice for Muslims who are able to do once in a lifetime. Implementation of the Hajj in Makkah Al Mukarramah housed (Saudi Arabia)on the 10th Dzulhijjah every year. Organize and restructure the Organization of theHajj is indeed not an easy job and once so it can satisfy all parties. Methodology the study used qualitative method and become objects in this research is the Managerof Hajj in the Regional Office of the Ministry of religion of North Sulawesi province and pilgrims period 2013 – 2015 and other Islamic organizations. Data collection is carried out by means of interviews to 15 informants consist of four staff in the Officeof Kemenag Prov. Flammable (SISKOHAT), 2 representatives of BPS-BPIH, 6 peoplepilgrims by 2013 – 2015, 3 people from religious figures/community. As for the goalin this research that the management of the Organization of the Hajj in North Sulawesi province were still low so that the role of management in organizing the Hajj should be further enhanced, as well as the understanding of the people about the management and service of pilgrimage in some things to be fixed. From this research it can be concluded that pull in the management of the Organization of the pilgrimage in North Sulawesi was still low. Recommended socialisation, improved infrastructure and increasing the professionalism of the officers work. Keywords: Management Of Organizing The Pilgrimage.